EVALUASI IMPLEMENTASI PROGRAM SISTEM PENCATATAN DAN PELAPORAN TERPADU PUSKESMAS - evi hasnita (HUMAN CARE JOURNAL, 2019)
Program implementation in Koto Type the health center includesseveral phases of activity, starting from the data collection phase, perekapan, inputting and sending to the Department of Health Kota.dari terms of delivery of the reports is still timely and charging an incomplete report. The purpose of this study to evaluate the implementation of the program recording and reporting system of integrated health centers in health centers katik koto long field,research design  is  qualitative  research  with  phenomenological.  With  the  number  of informen of 7 people, results showed on the input source human resources are lacking, the process of the implementation of the SP2TP not running optimally because still many shortcomings in the planning, recording and reporting so that the effect on the incompleteness and delays in the delivery of the Monthly Report.The conclusion of the research is the implementation of the PHC Koto SP2TP Katik not been implemented optimally. The need for increased availability, power that the implementation processes SP2TP no constraints as well as reports submitted complete and timely.